Corporate Social Responsibility in times of the pandemic, a comparative study: Puerto Vallarta, Mexico, and Málaga, Spain. - Zepeda-Hernández, Sandra Luz; Costa de Carvalho, Fabíola Cristina; Ortega-Palomo, Germán (Routledge, 2023)
This chapter aims to compare the business practices related to Corporate Social Responsibility, especially the environmental and social dimensions adopted by small and medium-sized enterprises (SMEs) that make up the tourism cluster in two tourist destinations of sun and beach, Puerto Vallarta (Mexico) and Malaga (Spain), as a form to deal with the health and economic crisis caused by COVID19. Practices related to saving energy and the use of alternative energies were particularly studied, as well as water consumption, recycling materials and promoting local economies. Methodologically, the study was based on qualitative and quantitative techniques. Various key stakeholders representing the tourism sector were interviewed and a questionnaire was applied to managers and heads of SMEs in the polygons that comprise the tourist influx areas in both study locus. According to the findings, it was observed in Mexico the development of a marked orientation towards the control and saving of water, while in Spain the main practice observed was the recycling or reuse of materials, coinciding with municipal policies and regulations for the operation of business in Malaga downtown city. On the other hand, similarities were identified in energy saving and control practices, as well as responsible purchasing practices to promote local economies.
https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters?srsltid=AfmBOorO1TX72qgsp-iJRZWX7zaQvIUDYt-LZpmJ6yXzac5W7Y_bicbK
Keywords: Responsabilidad social de la empresa; COVID-19 - Influencia y consecuencias; Pandemic; Sustainability management practices; Corporate social responsibility